Healthcare, health and inequality in health in the Nordic countries - Terkel Christiansen; Jørgen Tranberg Lauridsen; Mathias Kifmann; Carl Hampus Lyttkens; Thorhildur Ólafsdóttir; Hannu Valtonen (University of Oslo, 2018)
All five Nordic countries emphasize equal and easy access to healthcare, assuming that increased access to healthcare leads to increased health. It is the purpose of the present study to explore to which extent the populations of these countries have reached good health and a high degree of socio-economic equality in health. Each of the five countries has established extensive public health programmes, although with somewhat different measures to increase health of the populations. We compare these countries to the UK and Germany by using data from the European Social Survey for 2002 and 2012 in addition to OECD statistics for the same years. Health is measured by self-assessed health in five categories, which is transformed to a cardinal scale using Swedish time trade-off (TTO) weights. As socio-economic measures we use household income and length of education. Socio-economic inequality in health is elicited in two ways. First, we show social gradients by comparing the percentage of respondents in the lower income group reporting good or very good health to the corresponding rates in the upper income group. Second, we show concentration indices of socio-economic related inequality in health. Everything else kept equal, good health and the size of the concentration index are negatively associated by definition. In 2012, mean health, based on Swedish weights applied to all countries, is above 0.93 in all the Nordic countries and the UK, but lower in Germany. Each of the Nordic countries have introduced centrally initiated comprehensive public health programmes to increase health and reduce socio-economic inequalities in health. In general, the Nordic countries have achieved good health for their populations as well as a high degree of socioeconomic equality in health. Improvements in life-style related determinants of health are possible, however. Published: Online June 2018. In print January 2019.